Synopsis of the 2020 U.S. VA/DoD Clinical Practice Guideline for the Management of Adult Overweight and Obesity. Issue 9 (28th August 2021) - Mayer, Stéphanie B; Graybill, Sky; Raffa, Susan D; Tracy, Christopher; Gaar, Earl; Wisbach, Gordon; Goldstein, Michael G; Sall, James
ABSTRACT: Introduction: In May of 2020, the U.S. Veterans Health Administration (VHA) and Department of Defense (DoD) approved a new joint clinical practice guideline for assessing and managing patients who have overweight and obesity. This guideline is intended to give healthcare teams a framework by which to screen, evaluate, treat, and manage the individual needs and preferences of VA and DoD patients who may have either of these conditions. It can be accessed at https://www.healthquality.va.gov/guidelines/CD/obesity/ . Materials and Methods: In January of 2019, the VA/DoD Evidence-Based Practice Work Group convened a joint VA/DoD guideline development effort that included clinical stakeholders and conformed to the Institute of Medicine's tenets for trustworthy clinical practice guidelines. Results: The guideline panel developed 12 key questions, systematically searched and evaluated the literature, created a 1-page algorithm, and advanced 18 recommendations using the Grading of Recommendations Assessment, Development, and Evaluation system. Conclusions: This synopsis summarizes the key recommendations of the guideline regarding management of overweight and obesity, including referral to comprehensive lifestyle interventions that combine behavioral, dietary, and physical activity change, and additional tools of pharmacologic and procedural interventions. Additionally, recommendations based on evidence found in the literature for short-term weight loss are included. A clinical practice algorithm that is part of the guideline is also included. Additional materials, such as provider and patient summaries and a provider pocket card, are also available for public use, accessible at the U.S. Veterans Health Administration (VHA) Clinical Practice Guidelines (CPG) website listed above.